The effect of glyphosate-based herbicide on aquatic organisms – a case study - Rzymski Piotr; Klimaszyk Piotr; Kubacki Tomasz; Poniedziałek Barbara (Limnological Review, 2013)
The non-selective, post-emergence herbicides based on glyphosate [N-(phosphonomethyl) glycine] are one of the most widely used pesticides in agriculture, urban areas and forestry. Although there has been documentation on the physical, chemical and toxicological properties of glyphosate, the aquatic toxicity of such formulations still requires assessment and evaluation. In the present study, we describe deliberate use of glyphosate-based herbicide in a bathing area of Lake Lednica (Wielkopolska, Poland) by unknown perpetrators in April, 2011. Glyphosate was detected using gas chromatography mass spectrometry (GC-MS) in the water samples collected from the bathing area at a mean concentration of 0.09 mg dm-3. Aboveground parts of emerged macrophytes (Phragmites australis and Typha latifolia) covering the investigated area were completely withered. Studies of benthic macroinvertebrates revealed no significant differences in taxa number between event (13 taxa) and control (14 taxa) sites although differences in abundance of particular taxa were observed. Significantly lower numbers of Chironomidae (by 41%), Oligochaeta (by 43%), Vivipariae (by 75%), Hirudinae (by 75%), Asellus aquaticus (by 77%), Gammarus pulex (by 38%) and Dreissena polymorpha (by 42%) were found at the glyphosate-treated site. Furthermore, compared to the control, chironomids (Chironomidae) exposed to glyphosate were represented by specimens smaller in length while A. aquaticus only showed large adults. The ranges of glyphosate concentration in the tissues of sampled macroinvertebrates and Phragmites australis organs were 7.3-10.2 μg kg-1 and 16.2-24.7 μg kg-1, respectively. Our study indicates that glyphosate-based herbicides may have adverse effects on aquatic organisms including macroinvertebrates, thus their use in (or nearby) surface waters should be subject to strict limitation.